Intramolecular Hydrogen Bond Improved Durability and Kinetics for Zinc-Organic Batteries - Sun, Tianjiang; Pan, Jun; Zhang, Weijia; Jiang, Xiaodi; Cheng, Min; Zha, Zhengtai; Fan, Hong Jin; Tao, Zhanliang (Nano-Micro Letters, 2023)
Organic compounds have the advantages of green sustainability and high designability, but their high solubility leads to poor durability of zinc-organic batteries. Herein, a high-performance quinone-based polymer (H-PNADBQ) material is designed by introducing an intramolecular hydrogen bonding (HB) strategy. The intramolecular HB (C=O⋯N–H) is formed in the reaction of 1,4-benzoquinone and 1,5-naphthalene diamine, which efficiently reduces the H-PNADBQ solubility and enhances its charge transfer in theory. In situ ultraviolet–visible analysis further reveals the insolubility of H-PNADBQ during the electrochemical cycles, enabling high durability at different current densities. Specifically, the H-PNADBQ electrode with high loading (10 mg cm−2) performs a long cycling life at 125 mA g−1 (> 290 cycles). The H-PNADBQ also shows high rate capability (137.1 mAh g−1 at 25 A g−1) due to significantly improved kinetics inducted by intramolecular HB. This work provides an efficient approach toward insoluble organic electrode materials. Highlights: 1 Intramolecular hydrogen bond regulation is proposed to improve the quinone-based polymer (H-PNADBQ) solubility, conductivity, and kinetics. 2 Intramolecular hydrogen bonds reduce molecular polarization and increase π conjugation level, thereby suppressing the dissolution of the H-PNADBQ and accelerating reaction kinetics of H+/Zn2+ uptake/removal. 3 The H-PNADBQ electrodes exhibit excellent durability with high loading of 5 mg cm−2 and 10 mg cm−2, as well as high rate capability (137.1 mAh g−1 at 25 A g−1).